The profile of interested parties in the constitutional judicial review system carried out by the Brazilian Supreme Court - Costa, Alexandre Araújo; Costa, Henrique Araújo (Revista de Ciências Sociais, 2018)
This article traces the profile of plaintiffs in the constitutional control of constitutionality conducted by the STF through ADIs and ADPFs. Method. The methodological strategy consisted in the elaboration of a database with information on all the actions filed up to the end of 2016 and the use of descriptive statistics to identify standards in the data related to the filing. In this paper, it is not used as a unit of analysis each specific actor, but the classes of plaintiffs, in order to describe the profile of filing during the validity of the 1988 Constitution based on the classes of agents able to propose the actions that form the object of this research. Another relevant methodological element was the proposal to exclude from the count multiple actions on the same question, in order to avoid distortions in the descriptions operated. The analysis allowed the identification of several patterns in the filing of lawsuits, as well as the evolution over time of the plaintiffs' profile. The research corroborates the need to deal distinctly with the prosecution of federal, state, and municipal acts, which have been described separately. For the analysis of actions to control state acts (ACAEs), we propose the division of the period in five phases, each with a specific filing pattern. These same phases do not occur in the actions of control of federal acts, a set of processes that requires a more global analysis of the evolution of each class of actors.